A RESEARCH QUICK RESPONSE CODE AS AN INNOVATIVE TEACHING LEARNING TOOL IN SMK PATRIOT PETERONGAN JOMBANG - Hikmah Unwaha (Journal of Education, Linguistics, Literature and Language Teaching, 2021)
Abstract The use of ICT in education is must in digital era. It is quality learning effort. QR Code is technology-based media developed as very fast scanning tool. However, its existence is still rarely used in education. The existence of ICT in the form of QR code in English lessons can support learning success as not all students have computer. QR code is solution to the problem of students because it can be installed on Android. This study examines the use of QR Code media in optimizing high school English learning, especially in listening skills. A study on the use of QR Code was conducted in 2021 at SMK Patriot Peterongan Jombang with a total of 25 students as the subject. The type of this research is development research. To analyze the results of the research, it is used quantitative descriptive analysis. Data obtained through questionnaires and learning outcomes tests. The researcher examined the influence of QR Media using paired sample t-test. The results showed that there is a significant effect after being given treatment because the significance is < 0,05, that is 0,00. Through QR Code, students can evaluate learning outcomes well and make it easy to understand the material being studied. The results of this study are very relevant in learning, especially in increasing students' learning outcomes to learning English at the senior high school level.